Seni sebagai Ekspresi Eksistensi Tantangan Kebijakan Multikulturalisme - Yasmine Zaki Shahab (Antropologi Indonesia, 2004)
This article illuminates the author's concern that policies of multiculturalism which reverberated around the euphoria of the reformasi era appears to be in fact a response of the New Order government policy which emphasize on 'mono-culture' policy. The author sees that is not an impossible thing that policies of multiculturalism will be trapped on primordialism and certain ethnic domination. The author builds the argument from empirical data collected from art inventions of several ethnic groups in Indonesia that illustrate there is a tight relationship between art inventions and ethnic existence identity/solidarity. Arts invention brings toward identity reinforcement, existence, and finally authority from the ethnic group. This empirical data demonstrates that arts invention brings ethnic authority not only arts authority, but also authority in political life. Studying from the data raises the concern that multicultural policies which gives freedom to culture will bring to authority formation and concentration among ethnic groups with the strong potential in creating their arts. When this happens, Indonesia will return to certain ethnic domination. Is the government ready for the possible implication of such multicultural policies?